Responsive Web Design (International Journal of Engineering and Computer Science, 2017)
The usage of computers and mobile phones has increased considerably in the past few decades. But the current scenario suggests that the percentage of mobile internet users has increased immensely. The reason for this is nothing but the advantages of portable mobiles or tablets over the fixed computer machines. Now that people are resorting to mobiles there is a major need for the development of web applications which are mobile/tablet friendly. This will help ameliorate the user experience and in turn gain more clients. Up till now the tradition of building websites for PCs and apps for mobiles was being followed. But responsive web design has made it possible to design a single responsive website which can easily be accessed from various digital devices with different display screen sizes. Responsive web design favors the resizing of the elements present on any page of the website. The elements of the page may contain tables, images or simple texts as well. Thus it is evident that responsive web design is going to set a trend in the industry giving all sorts of benefits to the developers as well as the users. This paper gives a brief introduction to the softwares that can be used for designing a website responsively and the implementation details as well.